Assessing the practice of hot spots policing in Bogotá and Medellín - Ruiz-Vasquez, Juan Carlos; Páez, Katerin (FLACSO - Sede Ecuador, 2016)
Hot spots policing strategy uses pervasive deployment of police officers on the beat to reduce crime, which is highly concentrated in a few areas. In Colombia, cities like Bogota and Medellin have systematically implemented this model since 2009 regardless changes of their administrations. This article assesses the practice of both experiences on the way in which the model has been implemented from 2009. It concludes that, as result of the lack of scientific evaluations, it is impossible to definitely determine that crime has decreased in such sensitive areas; notwithstanding, crime reduction seems to be higher where police presence has increased.